Philosophical problems of cultural modernization (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the philosophical problems of cultural modernization and its features in Kazakh society. Culture is part of the modernization process of the modernization of society. Under the modernization refers to the process of transformation of the traditional society and culture in modern society. Modernization in the cultural sphere involves secularization of education, the presence of ideological and religious pluralism, and the spread of mass literacy. The authors show that, like others, our society can not move into the future, regardless of the global society, because it is a part of globalization. Changes in the global system somehow determine the general direction of change in his a subsystem, cultural and country. Kazakhstan is a unique way in the sense of specifying a particular national interest. Interaction with the world system governed by international law, and the transformations are carried out within the country Kazakhstan inherent features of social institutions, culture, mentality and style actions of citizens. Key words: philosophy, culture, modernization, globalization, multiculture, socialization, national culture.